2016
DOI: 10.1007/s00586-016-4488-2
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between cervical sagittal alignment and health-related quality of life in adolescent idiopathic scoliosis

Abstract: Changes in cervical sagittal parameters were significant after deformity correction in AIS patients. Correlation analysis revealed significant relationships between postoperative radiographic parameters and HRQOL. In particular, T1 slope and C2-C7 SVA were found to be significant predictors of HRQOL in AIS patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 26 publications
0
37
1
Order By: Relevance
“…It has also been suggested that T-1 slope and C2-7 SVA are related to health-related quality of life in patients with AIS. 23 However, we found no difference in C2-7 SVA according to preoperative CSA. Reportedly, C2-7 lordosis is related to the global thoracic sagittal alignment in Lenke type 5C curves.…”
Section: Discussioncontrasting
confidence: 61%
“…It has also been suggested that T-1 slope and C2-7 SVA are related to health-related quality of life in patients with AIS. 23 However, we found no difference in C2-7 SVA according to preoperative CSA. Reportedly, C2-7 lordosis is related to the global thoracic sagittal alignment in Lenke type 5C curves.…”
Section: Discussioncontrasting
confidence: 61%
“…Wang et al reported that the cervical sagittal alignment in AIS patients was related with lumbar lordosis and particularly with thoracic kyphosis [7], . It has been reported in many studies that the cervical sagittal alignment correlate with health-related quality of life (HRQOL) in AIS patients [10] [11], and that suboptimal sagittal alignment after corrective surgery, such as decreased thoracic kyphosis (TK), is a possible cause of lumbar or cervical spinal degeneration and junctional malalignment [1].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing sagittal offset has been shown to negatively affect SF-36 (Short Form-36 health survey) and NDI scores in patients who underwent posterior cervical fusion 5 and other studies have shown worse HRQOL scores with abnormal cervical alignment. 16,17 However, age-related normative cervical parameters in a North American population have not been established. Hardacker et al 4 reported on overall cervical lordosis in asymptomatic subjects but failed to include a comprehensive analysis of other cervical parameters and did not stratify subjects by age.…”
Section: Discussionmentioning
confidence: 99%